2015
DOI: 10.1097/nen.0000000000000144
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of Neuropathophysiology in Spinal Muscular Atrophy Type I

Abstract: Neuropathological findings within the CNS and PNS in patients with spinal muscular atrophy type I (SMA-I) were examined in relation to genetic, clinical and electrophysiological features. Five infants representing the full clinical spectrum of SMAI were examined clinically for compound motor action potential amplitude and SMN2 gene copy number; morphologic analyses of postmortem CNS, neuromuscular junction and muscle tissue samples were performed and SMN protein was assessed in muscle samples. The 2 clinically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
81
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(90 citation statements)
references
References 60 publications
4
81
0
5
Order By: Relevance
“…Whether these changes are due to deficiency of SMN or are a secondary effect of motor neuron dysfunction is currently unknown. Delay in maturation of the acetylcholine receptor was described, as has also been published by other investigators [14,15].…”
Section: Human Pathology In Sma Typementioning
confidence: 71%
“…Whether these changes are due to deficiency of SMN or are a secondary effect of motor neuron dysfunction is currently unknown. Delay in maturation of the acetylcholine receptor was described, as has also been published by other investigators [14,15].…”
Section: Human Pathology In Sma Typementioning
confidence: 71%
“…In contrast to human SMA, mouse models of SMA demonstrate several additional pathological features that are only rarely reported in a few patients with the most severe forms of the disease (type 0 SMA with a single copy of SMN2 ) (Araujo et al, 2009; Bevan et al, 2010; Distefano et al, 1994; Harding et al, 2015; Rudnik-Schoneborn et al, 2010; Shababi et al, 2012; Shababi et al, 2014). Therefore, loss of motor neuron function and degeneration is the most clinically relevant feature in SMA models.…”
Section: Discussionmentioning
confidence: 99%
“…4 Most of these latter patients die in the first weeks of life. [11][12][13][14][15] In this work, we present 3 patients (pts) with clinical and genetic diagnosis of SMA type 0 who survived longer than expected and presented similar progressive brain imaging changes over time. 6,7 Several studies have demonstrated a strong inverse correlation between the number of SMN2 copies (a homologous gene of SMN1) and SMA severity.…”
mentioning
confidence: 88%